Initial Clinical Outcome With Bilateral, Dual-Target Deep Brain Stimulation Trial in Parkinson Disease Using Summit RC + S. Issue 1 (7th July 2022) - Mitchell, Kyle T.; Schmidt, Stephen L.; Cooney, Jeffrey W.; Grill, Warren M.; Peters, Jennifer; Rahimpour, Shervin; Lee, Hui-Jie; Jung, Sin-Ho; Mantri, Sneha; Scott, Burton; Lad, Shivanand P.; Turner, Dennis A.
Abstract : BACKGROUND: Deep brain stimulation (DBS) is an effective therapy in advanced Parkinson disease (PD). Although both subthalamic nucleus (STN) and globus pallidus (GP) DBS show equivalent efficacy in PD, combined stimulation may demonstrate synergism. OBJECTIVE: To evaluate the clinical benefit of stimulating a combination of STN and GP DBS leads and to demonstrate biomarker discovery for adaptive DBS therapy in an observational study. METHODS: We performed a pilot trial (n = 3) of implanting bilateral STN and GP DBS leads, connected to a bidirectional implantable pulse generator (Medtronic Summit RC + S; NCT03815656, IDE No. G180280). Initial 1-year outcome in 3 patients included Unified PD Rating Scale on and off medications, medication dosage, Hauser diary, and recorded beta frequency spectral power. RESULTS: Combined DBS improved PD symptom control, allowing >80% levodopa medication reduction. There was a greater decrease in off-medication motor Unified PD Rating Scale with multiple electrodes activated (mean difference from off stimulation off medications −18.2, range −25.5 to −12.5) than either STN (−12.8, range −20.5 to 0) or GP alone (−9, range −11.5 to −4.5). Combined DBS resulted in a greater reduction of beta oscillations in STN in 5/6 hemispheres than either site alone. Adverse events occurred in 2 patients, including a small cortical hemorrhage and seizure at 24 hours postoperatively, which resolved spontaneously, and extension wire scarring requiring revision at 2 months postoperatively. CONCLUSION: Patients with PD preferred combined DBS stimulation in this preliminary cohort. Future studies will address efficacy of adaptive DBS as we further define biomarkers and control policy.